Clinical evaluation of one-step impression technique and definitive casts - Özcan Işıl; Köroğlu Aslıhan; Kale Ediz; Özçelik Tuncer Burak; Yilmaz Burak (Balkan Stomatological Society, 2022)
Background/Aim: The purpose of this study was to evaluate the quality of impressions made with vinyl polysiloxane (VPS) material in clinical conditions by using the one-step impression technique, and the quality of casts generated from these impressions. The effect of operator, number and location of abutments, and presence of bleeding were also investigated. Material and Methods: A total of 150 fixed dental prosthesis (FDP) impressions were taken and considered acceptable by 3 experienced prosthodontists in a clinic in an institutional setting. The impressions were evaluated and rated by another experienced prosthodontist and respective casts were evaluated and rated by an experienced dental technician using a digital microscope with ×200 magnification. The defects observed were noted as bubbles, voids, tears, or other defects. A scale was structured for the impressions and casts with ratings of Alpha (excellent; no defects), Bravo (acceptable; small defects), Charlie (inadequate; defects that require remaking of impression), and Delta (unacceptable; substantial defects at preparation finish lines). The data were analyzed with the Chi-square test for inter-operator, number of abutments, and location of prepared tooth variables (a=0.05). Results: The scale ratings were 85 Alpha (57%), 52 Bravo (34%), 6 Charlie (4%), and 7 Delta (5%) for the impressions, and 81 Alpha (54%), 58 Bravo (39%), 4 Charlie (3%), and 7 Delta (5%) for the respective casts. Sixty-nine percent of the impressions and respective casts were rated with the same score. The scale rating results were not influenced by inter-operator variability or number of abutments. Location of the prepared tooth was significant for anterior/posterior (p=0.04), but was not significant for maxilla/ mandible (p>0.05). Bleeding at the preparation site had a significant effect on the acceptability of the impression (p=0.003). Conclusions: The acceptability of VPS impressions using onestep technique was independent of the operator, number of abutments, or whether the prepared tooth was in maxilla or mandible. Impressions of teeth in the anterior region were more acceptable than those located in the posterior. Bleeding negatively affected the acceptability of the impressions. Clinicians may use VPS impressions for the fabrication of FDPs using onestep dual-phase technique. However, clinicians should carefully evaluate their impressions when bleeding is present when using this technique.